Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Mulia Barokah Fotocopy - Adhisty Kartika Dewi (Fakultas Teknik dan Rekayasa, 2025)
This study aims to analyze the effect of price and service quality on purchasing decisions at Mulia Barokah Fotocopy. In the service business world, price and service quality factors play an important role in attracting and retaining customers. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires distributed to Mulia Barokah Fotocopy customers. The data analysis technique used multiple linear regression analysis to determine the extent to which price and service quality influence purchasing decisions. The results of the study indicate that price has a significant effect on purchasing decisions, where customers tend to choose photocopying services that offer competitive prices. In addition, service quality also has a positive effect on purchasing decisions, where friendliness, speed, and accuracy of service are factors considered by customers. Simultaneously, price and service quality have a significant contribution to purchasing decisions. The conclusion of this study is that in order to improve customer purchasing decisions, Mulia Barokah Fotocopy needs to maintain a competitive pricing strategy and improve service quality in order to provide a better experience for customers. Keywords: Price, Service Quality, Purchasing Decisions, Photocopy, Customers.